Cognitive impairments from developmental exposure to serotonergic drugs: citalopram and MDMA - Schaefer, Tori L. (Int J Neuropsychopharmacol, 2013)
We previously showed that developmental 3,4-methylenedioxymethamphetamine (MDMA) treatment induces long-term spatial and egocentric learning and memory deficits and serotonin (5-HT) reductions. During brain development, 5-HT is a neurotrophic factor influencing neurogenesis, synaptogenesis, migration, and target field organization. MDMA (10 mg/kg×4/d at 2 h intervals) given on post-natal day (PD) 11–20 in rats (a period of limbic system development that approximates human third trimester brain development) induces 50% reductions in 5-HT during treatment and 20% reductions when assessed as adults. To determine whether the 5-HT reduction is responsible for the cognitive deficits, we used citalopram (Cit) pretreatment to inhibit the effects of MDMA on 5-HT reuptake in a companion study. Cit attenuated MDMA-induced 5-HT reductions by 50% (Schaefer et al., 2012). Here we tested whether Cit (5 or 7.5 mg/kg×2/d) pretreatment attenuates the cognitive effects of MDMA. Within each litter, different offspring were treated on PD11–20 with saline (Sal)+MDMA, Cit+MDMA, Cit+Sal or Sal+Sal. Neither spatial nor egocentric learning/memory was improved by Cit pretreatment. Unexpectedly, Cit+Sal (at both doses) produced spatial and egocentric learning deficits as severe as those caused by Sal+MDMA. These are the first data showing cognitive deficits resulting from developmental exposure to a selective serotonin reuptake inhibitor. These data indicate the need for further research on the long-term safety of antidepressants during pregnancy.